Analysis of Individual Health Behaviors in Relation to Cardiovascular Disease Prevention among Employees of an Oil and Gas Company: Case Study Employees of an Oil and Gas Company - Yuliawan, Daud; Hanoum, Syarifa (Universitas Muhammadiyah Surakarta, 2025)
Deaths from heart disease among employees in the upstream oil and gas industry are a serious concern. Companies in these risky and costly environments need to better manage workplace health to meet their goals and follow regulations. This study aims to examine the influence of Health Belief Model variables—including socio-demographics, knowledge, perceived susceptibility, severity, barriers, benefits, self-efficacy, and cues to action—on individual health behaviors in preventing cardiovascular disease. Data was collected through a questionnaire from 129 respondents in an oil and gas company using purposive sampling. Descriptive analysis and SEM-PLS show that knowledge significantly influences perceived susceptibility, severity, benefits, and self-efficacy, while the variables of perceived susceptibility, benefits, and cues to action impact individual health behavior. These results indicate the need for comprehensive education programs and effective communication. Furthermore, the non-significant influence of barriers, severity, and self-efficacy suggests the need for identifying barriers and supportive work environment strategies. A systematic approach involving psychological, environmental, and social factors is also important to improve employee health, productivity, and overall well-being.